Effectiveness of visual and acoustic biofeedback eccentric viewing training in conjunction with home exercises on visual function: a retrospective observational review. (2nd January 2023) - Kelly, Natalia; Vukicevic, Meri; Koklanis, Konstandina
ABSTRACT: The aim of this study is to evaluate the effectiveness of an eccentric viewing training program that combines biofeedback training using micro-perimetry with home exercises on multiple visual function parameters and to explore potential relationships between post-treatment visual function parameters. A retrospective observational review of 27 participants who underwent the training program was performed. Eligible participants were diagnosed with bilateral central scotomas secondary to age-related macular degeneration. All participants undertook up to 15 visual and acoustic biofeedback training sessions and were required to partake in traditional home exercises between sessions. The biofeedback training was conducted in the better eye using the Macular Integrity Assessment microperimeter (MAIA). Distance and near acuity, contrast sensitivity and fixation stability quantified by the P1 and P2 values and the 63% and 95% bivariate contour ellipse area (BCEA) before and after the rehabilitation program were recorded. Significant improvement was noted post-training for distance visual acuity (t(26) = 4938 p  = .000), near visual acuity (Z = −4.461 p  = .000), contrast sensitivity (Z = −3.647 p  = .000) and fixation stability for all measures, including P1 (t(26) = −9.490 p  = .000), P2 (t(26) = −7.338 p   = 0.000), 63% BCEA (Z = 3.569 p  = .000) and 95% BCEA (t(26) = 4.687 p  = .000). Significant medium-to-large correlations were also found between most visual function variables. Visual and acoustic biofeedback in conjunction with home exercises has the potential to improve visual function parameters in patients with age-related macular degeneration and irreversible central vision loss.